Advances in genetics. - Friedmann, Theodore, 1935-; Dunlap, Jay C.; Goodwin, Stephen F. (Academic Press, 2017)
"Advances in Genetics, Volume 98 provides the latest information on the rapidly evolving field of genetics, presenting new medical breakthroughs that are occurring as a result of advances in our knowledge of the topic. The book continually publishes important reviews of the broadest interest to geneticists and their colleagues in affiliated disciplines, critically analyzing future directions. Topics of interest in this updated volume include the Genetics of Mitochondrial Disease, a Genetic analysis of depression, happiness and other normal personality traits, The Evolving Centromere and Kinetochore, and The Genetics of Parkinson's Disease. Critically analyzes future directions for the study of clinical genetics. Written and edited by recognized leaders in the field. Presents new medical breakthroughs that are occurring as a result of advances in our knowledge of genetics"--